Kajian Teknis Operasional dan Lingkungan Rumah Potong Hewan Taliwang Kabupaten Sumbawa Barat - Saputra, H. S.; Nuraini, H.; Priyanto, R.; Salundik, Salundik (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2015)
There are three issues that must be concerned by the slaughterhouse in carrying out its activities which are the technical requirements, service quality and environmental impacts. This study was done to investigate: 1) the suitability of physical requirement and human resources; 2) public satisfaction index and 3) wastewater quality. The study was conducted in Taliwang, West Sumbawa Regency, West Nusa Tenggara Province from April to September 2014. Wastewater quality was analyzed in The Central Laboratory of Lombok Island Public Health. The Public Health Office of West Nusa Tenggara Province. The data obtained were analyzed descriptively than compared with the applicable regulations. The results showed that the suitability of physical requirement and human resources were 91.5 and 160, respectively. Public satisfaction index was 84.70  and wastewater quality such as BOD, COD, TSS, oils and greases, and pH were 2905 mg l-1; 19000 mg l-1; 510 mg l-1; <1 mg l-1 and 6, respectively. The physical requirements were not suitable (TS) and human resources were less suitable (KS) with The Agriculture Minister Regulations No. 13 in 2010, service performance was very good and wastewater quality (BOD, COD and TSS) were higher than standard of The Environment Minister Regulation No. 2 in 2006.